Rancang Bangun Data Repository Biro Penelitian Publikasi dan Pengabdian Masyarakat Universitas Kristen Satya Wacana (Studi Kasus: Biro Penelitian Publikasi Dan Pengabdian Masyarakat UKSW) - Frederik S. Papilaya, Penindas Fiodinggo Tanaem, Andeka R. Tanaamah, (SMATIKA, 2014)
Publication Research and Society Dedication Agent is an institution that is active inpublication, research and society dedication field that operates in the area of Satya WacanaChristian University and has function to build up the culture of research and dedication of lecturers,to develop publication practice, and also to help developing research institution in study programarea, Faculty, and university based on critical, creative, principle and positive participation and alsoto make Salatiga city as the object of society dedication of Satya Wacana Christian University. Â There is a repository or digital library which becomes a subdivision of technologydevelopment nowadays which gives great contribution for each individual and group who uses it indelivering information. To answer this defiance, it is prominent to have a digital library. Â By usingSystem Development Life Cycle (SDLC) method, it will help to build a desired application throughmaking use of waterfall model, since this model applies a serial feature in every process that exists.Therefore, this research is expected to produce an application that is able to successfully keep allresearch data recorded in Publication Research and Society Dedication Agent to be delivered inmore effective and efficient forms.